2022
DOI: 10.3390/ijerph191811497
|View full text |Cite
|
Sign up to set email alerts
|

Possible Stress–Neuroendocrine System–Psychological Symptoms Relationship in Pregnant Women during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic induced long-term damages that weigh on the national health systems of various countries in terms of support and care. This review aimed to highlight the mental health impact of the COVID-19 pandemic in pregnant women. We first report data on the immune system physiopathology and the main viral infections in pregnancy, including COVID-19. Then, the attention is focused on the main factors that affect the mental health of pregnant women during the COVID-19 pandemic, such as (1) the fear of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The results of this study showed that the detection rate of anxiety, insomnia, and stress disorder in pregnant women was significantly higher than that in the general population, which was consistent with the conclusions of previous studies. 3 , 12 , 13 However, the detection rates of anxiety, insomnia, and stress disorders and the related average scores of pregnant women were lower than those in the early stage of COVID-19. 14–16 The reasons may be as follows: Since the first outbreak of COVID-19, China has gradually improved prevention and control measures, increased epidemic prevention supplies, and rationally deployed medical resources to reduce people’s exposure risks.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The results of this study showed that the detection rate of anxiety, insomnia, and stress disorder in pregnant women was significantly higher than that in the general population, which was consistent with the conclusions of previous studies. 3 , 12 , 13 However, the detection rates of anxiety, insomnia, and stress disorders and the related average scores of pregnant women were lower than those in the early stage of COVID-19. 14–16 The reasons may be as follows: Since the first outbreak of COVID-19, China has gradually improved prevention and control measures, increased epidemic prevention supplies, and rationally deployed medical resources to reduce people’s exposure risks.…”
Section: Discussionmentioning
confidence: 92%
“…The results of this study showed that the detection rate of anxiety, insomnia, and stress disorder in pregnant women was significantly higher than that in the general population, which was consistent with the conclusions of previous studies. 3,12,13 However, the detection rates of anxiety, insomnia, and stress disorders and the related average scores of pregnant women were lower than those in the early stage of COVID-19. [14][15][16] The reasons may be as follows:…”
Section: Discussionmentioning
confidence: 96%
“…[28] They allow us to predict and respond better to conditions that arise as a result of light and dark cycles. [29] Studies have shown that normal vaginal delivery has a circadian rhythm; [10,11] however, it changes with external factors such as neuraxial labor analgesia, induction, oxytocin, and interventional birth. [30] In humans, the onset of normal vaginal delivery is mostly between 23:00 and 06:00, regardless of gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…[28] They allow us to predict and respond better to conditions that arise as a result of light and dark cycles. [29] Studies have shown that normal vaginal delivery has a circadian rhythm; [10,11] however, it changes with external factors such as neuraxial labor analgesia, induction, The values are given as n (%). Statistically significant values are written in bolt (P < .05).…”
Section: Indications Of Csmentioning
confidence: 99%
See 1 more Smart Citation